2019
DOI: 10.18488/journal.1005/2019.9.2/1005.2.204.215
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Adaptability Genotype of Hybrid Rice in the West Java Province of Indonesia

Abstract: Experiments to study the stability and adaptability genotype of hybrid rice were conducted in two locations in West Java: 1. the Jelekong Village Baleendah Bandung region, 2. the Arjasari Village Leuwisari Tasikmalaya region. The altitude of the Baleendah Bandung region is 650 and that of the Leuwisari Tasikmalaya region is 450 meters above sea level. The experiments were arranged in a randomized block design and used with 9 genotypes and 3 replications. The 9 genotypes of hybrid rice are SW-907, SW-804, SW-90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The character of plant height is also a determinant of plant yield which is closely related to the process of photosynthesis [26]. Stable lines have a good agronomic appearance, namely plant height, number of saplings, and moderate harvest age, and the total grain or panicle number is higher than the comparison variety [27]. The same thing was also stated by [28] that research that agronomically upland rice tolerant of Al's showed better agronomic character growth.…”
Section: Resultsmentioning
confidence: 72%
“…The character of plant height is also a determinant of plant yield which is closely related to the process of photosynthesis [26]. Stable lines have a good agronomic appearance, namely plant height, number of saplings, and moderate harvest age, and the total grain or panicle number is higher than the comparison variety [27]. The same thing was also stated by [28] that research that agronomically upland rice tolerant of Al's showed better agronomic character growth.…”
Section: Resultsmentioning
confidence: 72%
“…Society and culture is a relationship that is very difficult to separate. Because society is people who live together that produce culture (Amalia, 2019). Thus, no society has a culture; conversely, there is no culture without society as a vessel and supporter (Koentjaraningrat, 1994).…”
Section: Introductionmentioning
confidence: 99%